Denying Psychological Properties of Girls and Prostitutes: The Role of Verbal Insults. (March 2017) - Rubini, Monica; Roncarati, Alessandra; Ravenna, Marcella; Albarello, Flavia; Moscatelli, Silvia; Semin, Gün R.
This study examines the negative stereotypes of the category of women and their subcategories through the language of insults. Participants produced a list of epithets induced by the same hypothetical scenario in which the protagonist was presented either as a "prostitute" or as a "girl" (i.e., nonprostitute). Findings showed that the prostitute was addressed with taboo-related insults exaggerating sexual behavior, whereas the girl was mainly given warnings and intellectual insults. The implications of these results are discussed in relation to the underlying processes.